A Case of Urachal Yolk Sac Tumor With Spontaneous Rupture in a Child. Issue 2 (March 2017) - Suma, T.L.; Ramanathan, Subramaniam; Padma, M.; Appaji, L.; Suma, M.N.
Abstract : Tumors arising from urachus in children are exceedingly rare and sporadically reported in literature. Being a midline structure, the urachus may harbor neoplastic germ cell elements and can occasionally present as a case of acute abdomen. A 20-month-old toddler presented with spontaneous rupture of an urachal yolk sac tumor causing hemoperitoneum. He underwent resection, received platinum-based chemotherapy and presently remains well on follow-up. Despite its rarity, urachal germ cell tumors must be considered in a child with acute abdomen and tumor markers must be measured preemptively in such cases.